Evaluation of the antimicrobial activity of various concentrations of Tulsi (Ocimum sanctum) extract against Streptococcus mutans: An in vitro study - Agarwal Pooja; Nagesh L; Murlikrishnan (Wolters Kluwer Medknow Publications, 2010)
Aim: To determine if Tulsi (Ocimum sanctum) extract has an antimicrobial activity against Streptococcus mutans and to determine which concentration of Tulsi (Ocimum sanctum) extract among the 15 concentrations investigated has the maximum antimicrobial activity. Setting and Design: Experimental design, in vitro study, Lab setting. Materials and Methods: Ethanolic extract of Tulsi was prepared by the cold extraction method. The extract was then diluted with an inert solvent, dimethyl formamide, to obtain 15 different concentrations (0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 6%, 7% 8%, 9%, 10%) of the extract. 0.2% chlorhexidine was used as a positive control and dimethyl formamide was used as a negative control. The extract, along with the controls, was then subjected to microbiological investigation to determine which concentration among the 15 different concentrations of the extract gave a wider inhibition zone against Streptococcus mutans. The zones of inhibition were measured in millimeters using a vernier caliper. Results: At the 4% concentration of Tulsi extract, a zone of inhibition of 22 mm was obtained. This was the widest zone of inhibition observed among all the 15 different concentrations of Tulsi that were investigated. Conclusion: Tulsi extract demonstrated an antimicrobial property against Streptococcus mutans.